Generation of INS-jGCaMP7f knock-in Ca2+ reporter human embryonic stem cell line, GZLe001-C, using CRISPR/Cas9-based gene targeting - Xin Liu; Feng Zhang; Deqi Chen; Jiaxiang Yin; Zirong Bi; Lihua Chen; Jiawei Yan; Qifei Dong; Wei Peng; Tao Xu; Yanying Guo; Haopeng Lin; et al. (Stem Cell Research)
As a member of the single-fluorophore genetically encoded calcium indicators (GECIs), jGCaMP7f is widely applied to investigate intracellular Ca2+ concentrations. Here, we established an INS-jGCaMP7f knock-in H1 human embryonic stem cell (hESC) line by integrating jGCaMP7f gene into insulin locus via CRISPR/Cas9 system. The reporter cell line not only effectively labelled the insulin-producing cells induced from hESC, but also reflected the cytosolic change of Ca2+ level in response to different stimuli. This reporter cell line is a valuable research tool for studying functional maturation of hESC-derived insulin-producing cells, conducting drug screenings, and exploring the mechanisms of diabetes.